Numerical analysis library (Research Computer Center, Moscow State University) - Arushanian, O.B.; Volchenskova, N.I. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2002)
We consider the structure and organization of the numerical analysis library developed in Fortran and C at Research Computer Center of Moscow State University. The main features of the library as well as basic rules used to format the documentation and source program texts are given. The systematic catalog of the library, which reflects the chosen classification of numerical analysis, is presented. The Internet representation of the library is described. The library usage in the computing cluster installed at the Research Computer Center is discussed.